If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 8) = 13x + 1 Reorder the terms: -3(8 + x) = 13x + 1 (8 * -3 + x * -3) = 13x + 1 (-24 + -3x) = 13x + 1 Reorder the terms: -24 + -3x = 1 + 13x Solving -24 + -3x = 1 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -24 + -3x + -13x = 1 + 13x + -13x Combine like terms: -3x + -13x = -16x -24 + -16x = 1 + 13x + -13x Combine like terms: 13x + -13x = 0 -24 + -16x = 1 + 0 -24 + -16x = 1 Add '24' to each side of the equation. -24 + 24 + -16x = 1 + 24 Combine like terms: -24 + 24 = 0 0 + -16x = 1 + 24 -16x = 1 + 24 Combine like terms: 1 + 24 = 25 -16x = 25 Divide each side by '-16'. x = -1.5625 Simplifying x = -1.5625
| 7N-2N+3P+2P= | | -15x=240 | | 2x=7y+3 | | 2-3p=0 | | b/5-3/4=1/2 | | 3(4xy+2x^2+5x^3y)= | | 7(4x+5)= | | 0.5+3.6=4.2-1.5 | | -19x=380 | | x+25x-6y+5y-11= | | 0.96y+2.25-0.06y=7.65 | | 2.2x-13=.6x | | 2x-7y=10 | | 6(x+4)= | | 168=6(-5x-2) | | Y^2-12y=-19 | | 0.5x+0.15(70)=35.5 | | 4y=-80 | | 6=11 | | 9(v+2)-3v=2(3v+4)-9 | | v/7+8=19 | | -2.4x=42.96 | | x^8+4x^7+3x^6= | | -27x^2-15x=0 | | 9x+2(2+x)=5+9x | | 10x-10-x-21=0 | | .75x+10=21 | | -3(2x-4)+5x=2 | | 16.95x+0.5=22.95x+0.02 | | -4x-x= | | 14.4y-5.1=2.1 | | 3x^7+15x^6+18x^5= |